Insulin secretion by 'kiss-and-run' exocytosis in clonal pancreatic islet β-cells. (1st August 2003) - Tsuboi, T.; Rutter, G.A.
Abstract : Exocytotic release of neuropeptides and hormones is generally believed to involve the complete merger of the secretory vesicle with the plasma membrane. However, recent data have suggested that 'kiss-and-run' mechanisms may also play a role. To analyse secretory events in neuroendocrine β-cells, we imaged chimaeric reporters targeted to either the vesicle membrane [chimaeras of synaptobrevin-2 and pH-sensitive green fluorescent protein (synapto·pHluorin) or of phogrin ( pho sphatase on the gr anule of in sulinoma) and enhanced green fluorescent protein (EGFP) (phogrin·EGFP)] or the lumen [neuropeptide Y (NPY)·pH-insensitive yellow fluorescent protein (Venus)] by evanescent wave microscopy. Unexpectedly, the frequency of NPY·Venus release events was only 17–27% of that of vesicle fusion reported with synapto·pHluorin, but not phogrin·EGFP, indicating that exocytosis of cargo peptides that is likely to require complete collapse of the vesicle into the plasma membrane is relatively rare. However, both the frequency and the kinetics of NPY·Venus release were modulated by stimulus strength or by overexpression of synaptotagmin IV, demonstrating the plasticity of 'kiss-and-run' fusion.